Reflective thinking in educational settings : a cultural framework - Antonietti, Alessandro, 1960-; Confalonieri, Emanuela; Marchetti, Antonella (Cambridge : Cambridge University Press, 2014)
This volume examines the role that culture plays in the acquisition of cognitive, linguistic, and social skills. Taking reflective thinking as a central analytical concept, the contributors investigate the role of personal reflection in a series of mental activities, including the creation of social relationships, the creation of a mental narrative to make sense of events, and metacognition. These three types of cognition are usually conceived of as separate research fields. Reflective Thinking in Educational Settings draws these discrete subfields into dialogue, exploring the connections and interplay among them. This approach yields insight into a range of topics, including language acquisition, cognitive processes, theory of mind, cross-cultural interaction, and social development. The volume also outlines the implications of these findings in terms of further research and possible social policy initiatives.
Machine generated contents note: Introduction Alessandro Antonietti, Emanuela Confalonieri and Antonella Marchetti; Part I. Representation and Metarepresentations: 1. Social development and the development of social representations: two sides of the same coin? Felice Carugati and Patrizia Selleri; 2. Learning from multimedia artifacts: the role of metacognition Alessandro Antonietti and Barbara Colombo; 3. Theory of mind in typical and atypical developmental settings: some considerations from a contextual perspective Antonella Marchetti, Ilaria Castelli, Giulia Cavalli, Eleonora Di Terlizzi, Flavia Lecciso, Barbara Lucchini, Davide Massaro, Serena Petrocchi and Annalisa Valle; 4. The use of metacognitive language in story retell: the intersection between theory of mind and story comprehension Janette Pelletier, Kathleen Hipfner-Boucher and Antoinette Doyle; 5. Language access and theory of mind reasoning: evidence from deaf children in bilingual and oralist environments Marek Meristo, Kerstin W. Falkman, Erland Hjelmquist, Mariantonia Tedoldi, Luca Surian and Michael Siegal; 6. Commentary: aspects and perspectives of research into meta-representative thought Piergiorgio Battistelli; Part II. Narratives: 7. Narrative, culture, and society Jerome Bruner; 8. Schooling and literacy in mind and society David Olson; 9. Teaching writing to undergraduate psychology students as socialization into a genre Pietro Boscolo; 10. Exploring pictorial artworks: the role of intersubjectivity Federica Savazzi, Garbiella Gilli and Simona Ruggi; 11. Does culture shape the professional self? An exploration of teachers' narratives Emanuela Confalonieri and Sarah Miragoli; 12. Commentary: exploring symbolic spaces: writing, narrative, and art Jens Brockmeier and Bruce D. Homer; 13. Concluding remarks Allesandro Antonietti, Emanuela Confalonieri and Antonella Marchetti.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Critical thinking; Reflective learning; Cognitive learning; Thought and thinking; Cognition and culture